Discrete element method and its application to the analysis of penetration into granular media - Balevičius, Robertas; Džiugys, Algis; Kačianauskas, Rimantas (Journal of Civil Engineering and Management, 2004)
Application of discrete element method (DEM) to keel penetration in granular media is investigated. The basic relations for visco‐elastic granular media composed of spherical particles are presented, together with 5th order Gear predictor‐corrector scheme for time‐integration. The background version of DEM and numerical time integration algorithm are developed and implemented into DEMMAT code. The implementation of time‐integration algorithm is verified by simple tests concerning particle‐particle, particle‐wall interactions, for which analytical expressions exist. By limiting the size of the media domain, the three‐dimensional problem is reduced to particular case presented as two‐dimensional domain of spherical particles. The variation of keel reaction and distribution of the particle forces due to different material properties are investigated.First Published Online: 14 Oct 2010